Use of polygenic risk scores for differential diagnostics for patients with clinical diagnosis of familial hypercholesterolemia - M. Zaychenoka; A. N. Meshkov; A. V. Kiseleva; A. I. Ershova; E. A. Sotnikova; A. A. Zharikova; Yu. V. Vyatkin; V. I. Mikhailina; A. A. Bukaeva; M. S. Pokrovskaya; V. E. Ramenskiy; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
Aim. To evaluate the polygenic contribution to low-density lipoprotein cholesterol (LDL-C) and total cholesterol (TC) levels in patients with familial hypercholesterolemia (FH) based on polygenic risk scores (PRS), as well as to examine the potential of predicting referential FH diagnosis in non-carriers of pathogenic variants.Material and methods. The study used the results of genetic testing of a population sample from the Ivanovo Oblast (n=1673) and patients of the National Medical Research Center for Therapy and Preventive Medicine with a diagnosis of FH (n=353). The study included three different PRSs for LDL-C and three PRSs for TC.Results. The study evaluated the PRS feasibility for the Russian population: the percentage of variance explained by PRS ranged from 4,54% to 6,23% for LDL-C and from 2,74% to 5,98% for TC. Significant (p<0,001) differences in PRS values were shown for three groups as follows: a population sample from the Ivanovo Oblast, patients with clinical FH diagnosis who are carriers and non-carriers of known pathogenic variants in the LDLR, APOB and PCSK9 genes. PRS data can be used for differential diagnostics of patients with clinical diagnosis of FH to unveil individuals with polygenic hypercholesterolemia.Conclusion. For the first time, the predictive power of PRS for LDL-C and TC in the Russian FH patients has been studied.